ANALISIS PENGARUH PERTUMBUHAN EKONOMI, JUMLAH PENDUDUK, PAD, IPM, DAN UMK TERHADAP KETIMPANGAN DI PROVINSI BANTEN - Rosita Juliana; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2019)
This study aims to analyze the effect of per capita GRDP, population, PAD, UMK ana IPM on inequality in Banten Province in 2010-2016. The type of data used in this study is secondary data in the form of panel data consisting of seven-year time series, namely 2010-2016 which consists of 8 districts / cities in Banten Province, meanwhile, the data analysis used in this study is the FEM method. (Fixed Effect Model). The results of this research, among others. First, the inequality of development 2010-2016 year in Banten Province experiencing fluctuations in each year. Second, GDP per capita, population, and significant influential PAD against inequality. Third, the IPM and the UMK insignificant against inequality. And third, the coefficient of Determination (R2) of 0.998990 or 99.89%. This indicates that the traffic free variables i.e. GDP per capita, population, PAD, IPM and the UMK explain variables bound Inequalities of 99.89% and the rest of 0.11% can be explained by other variables.